2011
DOI: 10.1002/ptr.3404
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic Activity of C‐Geranyl Flavonoids from Mimulus bigelovii

Abstract: Bioactivity-directed fractionation of the MeOH fraction of the extract of Mimulus bigelovii by means of an axenic Leishmania amastigote assay and chromatographic techniques resulted in the isolation of four C-geranyl flavanones, diplacone (1), 3'-O-methyldiplacone (2), 4'-O-methyldiplacone (3), 3'-O-methyldiplacol (4), together with a geranylated flavone, cannflavin A (5). These compounds were separated from M. bigelovii for the first time. All compounds showed moderate antileishmanial activity against axenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Radwan et al (2008a) also reported a moderate activity of cannflavin A (17 mg/mL, 39 mM). Salem et al (2011) have published some data about the antileishmanial activity of the C-geranyl flavonoids that are in good agreement with the data presented here. Thus, we suggest that the presence of a prenyl side chain at C-6 could be an important structural feature for antileishmanial activity.…”
Section: Resultssupporting
confidence: 90%
“…Radwan et al (2008a) also reported a moderate activity of cannflavin A (17 mg/mL, 39 mM). Salem et al (2011) have published some data about the antileishmanial activity of the C-geranyl flavonoids that are in good agreement with the data presented here. Thus, we suggest that the presence of a prenyl side chain at C-6 could be an important structural feature for antileishmanial activity.…”
Section: Resultssupporting
confidence: 90%
“…Compounds 4 and 6 achieved significant antileishmanial activity with IC 50 values of 10.4 and 12.7 μM against L. donovani, and 11.3 and 8.0 μM against L. braziliensis, respectively, compared with 9.5 and 6.7 μM of miltefosine as the positive control (Navrátilová et al 2016). Furthermore, diplacone (2) was also active (IC 50 1.4 µg mL −1 ) against the related kinetoplastid parasite Trypanosoma brucei brucei (Salem et al 2011).…”
Section: Antiparasitic Activitiesmentioning
confidence: 99%
“…The activity of quercetin, for example, has been at least partially attributed to inhibition of DNA gyrase (Cushnie and Lamb, 2006). Recently, a number of reports published in Phytotherapy Research have demonstrated that flavonoids extracted from plants such as Larrea tridentate, Erythrina caffra and Melampyrum arvense exerted antiviral (Alvarez et al, 2012;Choi et al, 2012a), antibacterial (Chukwujekwu et al, 2011;Favela-Hernández et al, 2012;Tomczyk et al, 2011) and antiprotozoal activities (Kirmizibekmez et al, 2011;Salem et al, 2011). Interestingly, Choi and colleagues showed that quercetin 3-rhamnoside, given orally, decreased mortality in influenza A/WS/33 virus-infected mice, the effect being associated to a delayed development/progression of pulmonary histological lesions (Choi et al, 2012a).…”
Section: Antimicrobial and Antiparasitic Activitiesmentioning
confidence: 99%